A translation‐based data acquisition method for computed tomography: Theoretical analysis and simulation study. Issue 8 (31st July 2013) - Schön, Tobias; Fuchs, Theobald; Hanke, Randolf; Dremel, Kilian
Abstract : Purpose: : In this paper, the authors propose a new method for computed tomography (CT) data acquisition, which requires almost no rotational movement of the system or the object, respectively. Methods: : The new method is taking advantage of the fact that variations of magnification, e.g., by change of distance between x‐ray focal spot and detector, will provide both different beam angles and ray paths with respect to the object. In other words, the rotational movement is substituted by one or more linear movements of the x‐ray source toward the object under inspection. The authors present a theoretical evaluation of this new translational acquisition scheme. Results: : The mathematical implementation of image reconstruction are discussed and results from simulations with varying measurement parameters are shown. The image quality is evaluated by quantitative numbers. Conclusions: : Translational x‐ray CT generally allows for reconstructing images with adequate quality. However, the image quality suffers from the lack of data compared to conventional 180° acquisition methods and, due to the irregular sampling of Radon space, spatial resolution as well as artifacts depend on the position within the image.